Plugging an Information Leak. - Liu Xinlian (Beijing Review, 2012)
The article focuses on the proliferation of online security breach in China. The information of six million Chinese Software Developer Net (CSDN) users was leaked after its CSDN was hacked on December 21, 2011. Zhou Yonglin of the National Computer Network Emergency Response Technical Team/Coordination Center of China urged websites to encrypt information and require users to change their passwords regularly. He also encouraged the government to focus on new security issues.